Carpel ligament release for carpel tunnel syndrome (CTS) under local anesthesia: our experience with 277 cases - Basnet, Aashish; Bhattachan, Maya; Joshi, Sumit; Bhandari, Pawan; Shrestha, Ram Chandra; Aryal, Samir; Saharma, Gopal Raman (Nepal Journal of Neuroscience, 2019)
Carpel tunnel syndrome (CTS) is one of the common neurological condition where median nerve is compressed by transverse carpel ligament at wrist. About 5% of general population suffer from this problem and most commonly occurred in young and middle-aged women. 30% of patients suffering from CTS can be managed by medications and physiotherapy and 70% may require surgical decompression at some stage. Surgical treatment is to decompress median nerve by releasing transverse carpel ligament either by open or endoscopic procedure. Both procedures have shown similar results. This is a retrospective study of 277 patients who underwent 349 decompressive surgical procedures under local anesthesia for CTS between May 2007 and April 2017 in our institute. Diagnosis was made from clinical signs and symptoms and confirmed by either NCV or EMG. All patients were operated in day care basis. Data were retrieved from OPD and OT records. Followed up duration ranged from 6 months to 10 years. There were 257 female and 20 male. 74% had unilateral and 26% had bilateral CTS. 93% CTS were idiopathic. 10% suffered postoperative complications.26% achieved immediate pain relief after decompression, 73% after three weeks and 98.5% after three months. Open decompression of CTS is a quick and simple OPD based surgical procedure.